The Use of Artificial Neural Networks (ANN) in the Chayote Chips Dough Mixer - Roza Susanti; Zas Ressy Aidha; Surfa Yondri; Sir Anderson; Tri Oktaviandra (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
This study uses a backpropagation neural network to determine the evenness of the chayote chip dough. The Tcs3200 Color Sensor mounted on the stirrer alt is used as a sensor to determine the color of the chayote emping dough. A regression score of 1 indicates that the input and target data match in the test results of the artificial neural network, which has an objective error (MSE) value of 0.0096306 achieved in the 313th epoch. Changes in RGB color readings on the TCS sensor from min values ??<40 and max values>52 in mixing dough are influenced by distance and light intensity which will be converted in the form of frequency.